The Constellation of Agents: An Often Overlooked Aspect in the Comparison of Deuteronomy and Ancient Near Eastern Treaties - Joachim J. Krause (Religions, 2023)
Ever since the pioneering studies of George Mendenhall, Klaus Baltzer, Dennis McCarthy, and Moshe Weinfeld, the structural analogies between Deuteronomy and ancient Near Eastern treaties have been a key issue in the scholarly study of the book. More recently, the hypothesis that Deuteronomy 13* and 28* could even represent a Hebrew rendering of the Neo-Assyrian Succession Treaties of Esarhaddon has prompted a yet intensified investigation of the matter. Yielding nuanced models to account for the traditio-historical pluriformity of features in Deuteronomy vis-à-vis the various strands of tradition found in late Hittite and Neo-Assyrian, as well as Aramaic comparative evidence, this latter discussion has arguably once again broadened the horizon. In any case, it only emphasizes that reading Deuteronomy against the background of the ancient Near Eastern treaty tradition more broadly provides an indispensable perspective when it comes to the literary genesis of Deuteronomy as we have it. What is more, it also opens a window on its interpretation. At the same time, however, it can also lead to certain misconceptions, for as much as major parts of Deuteronomy are modeled on a treaty, Deuteronomy is no treaty. The comparative perspective thus requires one to heed both commonalities and differences. This article focuses on one such difference, namely the constellation of agents. It is typical of ancient Near Eastern treaties that the contracting parties agree to delegate the task of safeguarding the treaty to a third party constituted by deities. It is these gods who figure as “witnesses” of the curses that the contracting parties call upon themselves if they should act contrary to the treaty, the term “witness” also denoting, according to the semantics of ancient Near Eastern treaty discourse, “agent of the sanctions.” Hence, the agreed upon sanctions are conceived of as coming into effect without the further involvement of the contracting parties. In fact, this particular feature is the operating principle which makes an ancient Near Eastern treaty work. In Deuteronomy, however, it does not apply. While intriguingly enough there are certain entities in the close context of the curse sections which are called “witnesses,” none of them can truly figure as a witness in the sense described above, for none of them is a deity; neither is there an attempt made to charge these “witnesses” with putting into effect the curse sanctions. Often overlooked, this aspect has significant ramifications for the understanding of the curses in Deuteronomy and the treaty style structure in general.